2020
DOI: 10.1142/s0218127420500480
|View full text |Cite
|
Sign up to set email alerts
|

Coexisting Attractors, Energy Analysis and Boundary of Lü System

Abstract: In this study, first, the phenomenon of multistability in the Lü system is found, which shows the coexistence of two different point attractors and one chaotic attractor. These coexisting attractors are dependent on initial conditions of the system while the parameters of the system are fixed. Then, the Lü system is transformed to a Kolmogorov-type system, which includes the conservative torque consisting of the inertial torque and the internal torque, the dissipative torque, and the external torque. Moreover,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Therefore, Chen et al [31] improved Chua circuit using memristor and VOLUME 4, 2016 analyzed its hidden attractor by numerical and experimental methods. Besides, in classical chaotic systems, such as Chen system [32]- [36] , Lorenz system [37]- [39] and Lü system [40]- [42], scholars have also found the possibility of hidden attractor in these systems. Therefore, Lai et al [43] improved some classical chaotic systems, and found that coexistingattractors and hidden attractor exist for some parameter regions.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, Chen et al [31] improved Chua circuit using memristor and VOLUME 4, 2016 analyzed its hidden attractor by numerical and experimental methods. Besides, in classical chaotic systems, such as Chen system [32]- [36] , Lorenz system [37]- [39] and Lü system [40]- [42], scholars have also found the possibility of hidden attractor in these systems. Therefore, Lai et al [43] improved some classical chaotic systems, and found that coexistingattractors and hidden attractor exist for some parameter regions.…”
Section: Introductionmentioning
confidence: 99%